FEATURES INTELLECTUALIZATION OF COMPUTER-INTEGRATED MANUFACTURING BASED ON THE MULTIDIMENSIONAL FUZZY CONTROLLER - Osinov, C. (Енергетика і автоматика, 2016)
In this article the theoretical questions of instrumentation design for computers system and metodology of reengineering of business proceses for agriculture produsers was considered. The implementation of the instruments with using the biological feedback and self-organization proceses in computer system may to give the advantage in agriculture business. The feature of control system with sensor for identification the parametrs of biotechnical object was studyed.